Potential of Fucoidan From Brown Seaweeds (Sargassum sp.) as Innovation Therapy on Breast Cancer - Agung B S Satyarsa (Universitas Kristen Maranatha, 2019)
Breast cancer is a non-communicable disease and a major health problem in the world. Based on the data from WHO in 2012, the incidence of breast cancer is reported as 1.67 million cases. One cause of the highest morbidity and mortality in breast cancer is chemoresistance. Various attempts were made to solve this problem. The purpose of this review is to describe the potential of fucoidan from brown seaweeds (Sargassum sp.) as innovation therapy on breast cancer. Fucoidan as proapoptotic agents affect many target cells (multi-targets) to induce apoptosis. Fucoidan has a potential for a new treatment of breast cancer because of its potent proapoptotic and anti-metastatic properties. However, no research has yet evaluated this in clinical trial. Hence, further studies are needed to confirm the true potential of fucoidan from brown seaweeds as therapy for breast cancer. Keywords: anti-proliferative agents, pro-apoptotic agents, fucoidan, breast cancer